Butterflies, Dwarves, and Plastic Lollypops: A Case Report on Medical Clowning in a Children’s Rehabilitation Hospital - Sigalit Ofer; Shoshi Keisari (Children, 2022)
Medical clowning has been evolving in the past three decades and now plays a significant role in the rehabilitation processes of children who have suffered injuries and undergone complex medical procedures. The current paper focuses on this topic by presenting a case study of a young girl who lost most of her functional abilities due to brain damage. During the child’s physiotherapy sessions at the rehabilitation hospital, a medical clown was brought in to work together with the physiotherapist in providing the treatment. The case study brings an in-depth perspective on the therapeutic process, as it is based on documentation of the sessions while addressing key stages in the child’s rehabilitation, alongside core concepts in drama therapy. The qualitative analysis shows how the playful space in the rehabilitation process enhanced the child’s inner motivation, provided a space for role expansion, and promoted the connection between the child and the environment. This paper demonstrates how the involvement of medical clowns can promote the rehabilitation processes of children who have suffered traumatic injuries and help them cope with functional losses.